2011
DOI: 10.1007/s11552-011-9370-4
|View full text |Cite
|
Sign up to set email alerts
|

Cold Intolerance after Brachial Plexus Nerve Injury

Abstract: Background The purpose of this study was to evaluate cold intolerance symptoms in patients with brachial plexus nerve injury. We hypothesized that higher levels of cold intolerance would be associated with more pain, greater disability, and unemployment. Methods Following research ethics board approval and patient consent, we included English-speaking adults more than 6 months following brachial plexus nerve injury. Patient questionnaires included Cold Intolerance Severity Scale (CISS), McGill Pain Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…A number of these diseases and injuries have previously been reported in conjunction to CS alone, such as vascular disease [24], nerve injury [10], cold injury [25] and HAV syndrome [12]. Thus, it seems that CS and secondary RP share several common denominators, which suggest that CS is an acquired condition primarily arising as a result of peripheral neural or vascular injury.…”
Section: Interpretation and Comparisonmentioning
confidence: 99%
“…A number of these diseases and injuries have previously been reported in conjunction to CS alone, such as vascular disease [24], nerve injury [10], cold injury [25] and HAV syndrome [12]. Thus, it seems that CS and secondary RP share several common denominators, which suggest that CS is an acquired condition primarily arising as a result of peripheral neural or vascular injury.…”
Section: Interpretation and Comparisonmentioning
confidence: 99%
“…The pathophysiological mechanisms are not fully elucidated, but seem to involve a multifactorial etiology, including neural (Irwin et al 1997 ), vascular (Hope et al 2014 ), as well as humoral (Koman et al 1998 ) aspects. Cold sensitivity has previously been studied as a sequela to upper extremity injuries, such as digital and hand amputation (Lithell et al 1997 ; Tark et al 1989 ), hand fracture (Nijhuis et al 2010 ), peripheral nerve and brachial plexus injury (Novak et al 2012 ; Ruijs et al 2007 ), upper extremity arterial injury (Klocker et al 2012 ), flexor tendon repair (Riaz et al 1999 ), corrective surgery for Dupuytren’s disease (McKirdy 2007 ), carpal tunnel syndrome (Thomsen et al 2009 ), freezing cold injury (Carlsson et al 2014 ), and hand–arm vibration (HAV) syndrome (Carlsson et al 2010c ; Necking et al 2002 ). Injuries aside, cold sensitivity has also been described in relation to diabetes mellitus (Thomsen et al 2009 ), and rheumatic diseases (Merkel et al 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neuropathic pain following traumatic injury and coldinduced pain have been associated with increased upper extremity disability. 14,15 The purpose of this study was to evaluate the relationship between self-reported cold sensitivity, pain, and impact on QoL after upper extremity nerve injury. We hypothesized that in patients with long-standing nerve injury, (1) higher levels of cold sensitivity and pain would be associated with a higher impact on QoL, and (2) patients who selected a single descriptor of "coldness" would have more severe pain, higher cold sensitivity scores, and higher impact on QoL.…”
Section: Introductionmentioning
confidence: 99%